Frances E. W Harper : a call to conscience - McKnight, Utz Lars (Cambridge, UK ; Medford, PA : Polity Press, 2021)
'The first full account of a leading 19th century female writer and anti-slavery activist'--
Includes bibliographical references (pages [284]-291) and index.
Keywords: Harper, Frances Ellen Watkins, -- 1825-1911 -- Criticism and interpretation; Harper, Frances Ellen Watkins, -- 1825-1911 -- Political and social views; Social change in literature; African Americans in literature; Politics and literature -- United States -- History -- 19th century; Antislavery movements -- United States -- History -- 19th century